A new species of the genus Neoperla (Plecoptera: Perlidae) from Guizhou, China with redescription of N. latamaculata Du, 2005 - Zeng, Liang-Liang; Huo, Qing-Bo; Du, Yu-Zhou (Zootaxa, 2025)
A new species of the genus Neoperla Needham, 1905, N. circuloloba sp. nov., is described from Guizhou Province, China. Additionally, we provide a redescription of N. latamaculata Du, 2005, along with the first record of the distribution of Neoperla in Chongqing Municipality, supplemented by clear color photographs to aid in future identification efforts.